A new characterizing method for warpage measurement of injection-molded thermoplastics. (July 2019) - Sun, Xianjun; Zeng, Danielle; Tibbenham, Patricia; Su, Xuming; Kang, Hong-tae
Abstract: Injection molded plastics are widely used for mass production in auto industry. However, it is challenge to produce parts that do not warp. It is helpful to have an accurate way to measure the warpage when investigating and solving warpage issues. In this paper, a new technology is introduced to measure the part warpage quickly and accurately with the help of digital image correlation (DIC) method. The polypropylene plaque were fabricated by injection molding based on An L9 (3ˆ4) Taguchi design of experiments. The warpage of plaque are characterized for all the conditions and at different time after being ejected. Different kinds of warpage results are obtained by DIC method, such as maximum deflection, deflection distribution along desired path, warpage contour on the surface. The plaque warpage increases with the time. The maximum difference can reach as high as 64.9%. The cooling time has the largest influence on the warpage, while the packing pressure has the minor effect. Nevertheless, the warpage difference due to time varying depends on melt temperature, mold temperature, cooling time and packing pressure, in which mold temperature has the highest effects. Highlights: The manuscript provides a new method for measuring the warpage of injection molded parts. It is accurate, easy to handle, and efficient. It can give not only the magnitude of over-all warpage, but also the pattern of warpage distribution in the part, that can be used to compare with the simulated warpage results from commercial software for injection molding.